Kajian Dampak Pengembangan Islamic Center Terhadap Kondisi Sosial dan Lingkungan - Agung Riyadi; Agus Dwi Santosa; Gunarto Gunarto; Lois Yulianto (Jurnal Bengawan Solo Pusat Kajian Penelitian dan Pengembangan Daerah Kota Surakarta, 2023)
The Islamic Center is the center of Islamic religious activities. Islamic centers emerged in America as a place for the growing American Muslim population. In Indonesia, there are quite well-known Islamic Centers such as the Jakarta Islamic Center, the Samarinda Islamic Center, and the West Nusa Tenggara Islamic Center. The Islamic center is a place that functions as a center for fostering and developing the Islamic religion, besides that it also functions as a space for the development of da'wah in the era of development The construction of the Islamic Center in Surakarta City is a part of the construction of the Raya Zayed Mosque which has been completed. The construction of Masjid Raya Zayed and Solo Islamic Center came from a gift from the Crown Prince of the United Arab Emirates (UAE), Sheikh Mohamed Bin Zayed Al Nahyan to President Joko Widodo. The construction of the Islamic Center is in line with the policy direction of the 2021-2026 City of Surakarta RPJMD, which is to increase efforts to use and control spatial planning with indications of the Optimizing the development of the North Solo Region program. This will balance the development of the North Solo Region and the development of the South Solo Region. Politically, the bilateral Islamic center is a symbol of friendship. The Solo Islamic Center that will be built is a collaboration between the governments of the UAE and Indonesia; Symbolizes good relations between the two countries.